Design of a direct memory access module for 32-BIT RISC32 processor - Tan, E-Chian (2022)
The project is about the design and implementation of a direct memory access (DMA) specifically for Reduced Instruction Set Computer (RISC-32) processor. In this proposal, a short introduction about the knowledge needed to get the project going is stated at the beginning. Followed by the literature review which talks about previous research done by other researchers. A short explanation about DMA is introduced and how everything is to be implemented into the RISC32 microprocessor. A block diagram will show what is inside the DMA controller. A partitioning level diagram is drawn to make users understand what is inside the DMA Controller. The pin description of the DMA is drawn out. Lastly, challenges encountered in this project is written and come the conclusion to state what has been done in this overall project together with the progress timeline made during the weeks.